العــنـف السياســي (دراسة نفسية) - الحصناوي سعد عبد الزهرة; بريسم علي عبد الحسين (Journal of College of Education, 2018)
the present study highlights one of the most significant topics in the field of psychology, namely political psychology . the study gives the reader a clear and simplified vision of political psychology . the study also sheds light upon political violence in Iraq in terms of causes and means of treatment . the study includes the following topics : 1-Definition of political violence . -introduction -movement, direction and types of political violence . 2-Distinction between political violence and other related terms . - political violence and political terrorism . - political violence and political conflict . - political violence and political instability . 3- Political violence Theories . -Culture violence theory . - Relative deprivation theory . -Balance of power theory . -Theory of political for political violence . -Rational choice theory . 4-means of treatment of political violence in Iraq . the researcher presents his own view on political violence in Iraq in the light of what has been dealt with.